Greenwashing in Fast Fashion: A Critical Analysis of Shein’s EvoluShein Campaign - Anindya Puteri; Evelyne Kezia Priyantono; Ghanesya Hari Murti; Erna Cahyawati; Dyah Purwita Wardhani; Imam Basuki (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
As environmental awareness grows, fast fashion brands increasingly adopt sustainability messaging to appeal to eco-conscious consumers. However, such efforts often raise concerns about greenwashing—where environmental claims are exaggerated, vague, or unsubstantiated. This study critically examines Shein’s evoluSHEIN campaign using Stöckl and Molnar’s Eco-Advertising Framework, which integrates linguistic and visual analysis to assess how brands construct eco-friendly narratives. Five official advertisements from 2024 were analyzed using Critical Discourse Analysis and multimodal semiotics. The findings identify five recurring greenwashing strategies: vague eco-lexicon, symbolic eco-imagery, unverified eco-certifications, emotional moral framing, and unsubstantiated absolute claims. Terms like “sustainable” and “eco-safe” are used without definition or evidence, while visuals—such as leafy graphics and green color schemes—reinforce environmental connotations without transparency. Moral slogans like “Join the fight for a greener planet” shift responsibility to consumers, framing ethical purchasing as the solution while masking Shein’s ongoing high-volume, low-cost production model. These strategies construct a cohesive yet largely symbolic environmental message, aligning with broader fast fashion trends where marketing appeal outweighs operational change. The study argues that this multimodal approach to greenwashing risks misleading consumers and eroding trust in legitimate sustainability initiatives. By highlighting the interaction between language and imagery in shaping perceptions of environmental responsibility, this research underscores the need for clearer regulatory standards, credible third-party certifications, and increased consumer media literacy. It contributes to the critical understanding of how greenwashing operates systemically within fast fashion and how ethical branding narratives may conceal unsustainable practices.